PERAN NILAI BUDAYA LOKAL SEBAGAI ANTESEDEN SUSTAINABLE HUMAN RESOURCE MANAGEMENT DI SEKTOR PARIWISATA PEDESAAN - Sitio, Nurul Mardhiah; Zahrani, Meisa Aulia; Aprillia, Rini (JURNAL LENTERA BISNIS, 2026)
The development of rural tourism often focuses on cultural exploitation as an attraction, neglecting the role of cultural values as the foundation of human resource (HR) governance. This study aims to analyze how local cultural values serve as antecedents in shaping Sustainable Human Resource Management (Sustainable HRM) practices in Cikalong Village, Pangandaran Regency. The study employed a qualitative descriptive approach with a case study design. Data were collected through participatory observation, in-depth interviews, and profile questionnaires distributed to 34 respondents representing various societal elements (farmers, entrepreneurs, traditional leaders). The findings indicate that local traditions such as Rengkong (mutual cooperation) and Nampaling (environmental balance) have been internalized into positive work behaviors. The dominance of agrarian culture and the demographic structure of the community proved to be strong social capital in forming collaborative work behavior (social sustainability) and environmental awareness (green HRM) organically. This study concludes that local culture is not merely a heritage of the past, but a strategic asset that ensures the sustainability of HR management in tourism villages.